Effect of Scatter, Attenuation and Resolution Correction on a Pediatric Myocardial Perfusion SPECT Image - Akiko Mogi; Yasuyuki Takahashi; Kimiko Nakajima; Hiroshi Shimizu; Kyoko Saito; Ken-ichi Tomaru (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2014)
Scatter correction, attenuation correction, and resolution correction are commonly used to improve the quantify ability of a SPECT image. However, almost none of these are discussed specifically for the pediatric patient. This study aims to suggest practical image processing techniques to improve pediatric SPECT reconstructions. We chose to use phantoms based on the size of a 3-year-old according to the body surface area (BSA). This age group has much postoperative follow-up. For correction methods, we chose triple energy window (TEW) scatter correction, segmentation with scatter and photo peak window data for attenuation correction (SSPAC) technique, and collimator broad correction (CBC) resolution correction. The phantom studies achieved 10counts/pixel/projection/rotation for the target area. Continuous mode acquisition was employed. Data from multiple sequential rotations were added together to provide data sets with from 10 to 100 counts/pixel/projection. Also, the effect of the corrections on a patient image was evaluated qualitatively. The noise level of their constructed phantom images was compared using the normalized mean square error (NMSE) metric. The error was computed for lesser count images relative to the image for the highest count level. For the 10, 20, 30, 40, 50, 60, 70, 80, and 90 counts/pixel/projection data: the pediatric myocardial phantom with a defect had a NMSE of 0.7587, 0.5997, 0.4627, 0.3519, 0.2546, 0.1700, 0.0976, 0.0412, and 0.0016, respectively. This series for the metric shows a tendency for the image to rapidly get less noisy as there are more counts per pixel. Increasing the acquisition time to get sufficient counts may be really difficult in pediatric myocardial nuclear medicine, however. We have seen that image quality deteriorates for a rapid, low-count     acquisition, as a compromise between image quality and practicality; we recommend at least 70 counts/pixel/projection to obtain the desirable low-noise image.